The professional chef - Culinary Institute of America (Hoboken, NJ Wiley, 2024)
""How to cook everything from the best culinary school in America. This is The Mothership for recipes and basic culinary techniques. Anyone and everyone serious about food and cooking should have one in their kitchen." --Anthony Bourdain The cornerstone of our publishing partnership with The Culinary Institute of America, The Professional Chef has been one of the top professional cooking books since 1962, through nine editions and more than sixty years. A constant in-the-kitchen resource for culinary students and culinary professionals, The Professional Chef teaches proper culinary technique and includes nearly 900 recipes for instruction and inspiration. The focus has been on three target markets: Professional chefs learning in corporate training programs or professional chefs pursuing professional development courses Culinary arts students: 78% are enrolled in 2-year / community college programs, 22% in 4-year universities, including the CIA itself Hospitality management students taking cooking courses"--
Includes bibliographical references and indexes.
Keywords: Quantity cooking; Cookbooks